Vertical and lateral drift behavior of a linear superconducting magnetic bearing system under multi-operating modes. (22nd June 2020) - Lei, Wuyang; Chen, Ling; Wang, Wen; Liu, Zhehao; Huang, Zhichuan; Deng, Zigang
Abstract: Since the discovery of high temperature superconducting (HTS) material, HTS maglev with the characteristics of self-stabilization and zero magnetic drag, has shown excellent potential for future transportation applications. However, this stability characteristic of HTS maglev is difficult to fully ensure in a spatial position, because of the magnetic flux flow and creep of the HTS bulk. Hence, to study the drift phenomenon of the HTS maglev vehicle excited by this unguaranteed stability characteristic, the linear superconducting magnetic bearing system, composed of a ring permanent magnetic guideway line (double track) and a HTS maglev vehicle, the 'Super-Maglev', was utilized. This system aims to explore the drift phenomenon in the vertical and lateral directions of the whole maglev vehicle under various operating conditions: different running speeds, unbalanced loading and cyclic loading situations. As an illustration induced by the experimental results, the lateral drift (LD) at a faster running speed (15 km h −1 ) is twice than that at 10 km h −1 . Also, compared to the constant load condition, the vertical drift (VD) under cyclic load is larger. Moreover, with time going by, both LD and VD tend to be stable. Specifically, for the LD curve, it can be fitted by an exponential function. Finally, all the above experimental results support references for the future design and study of linear SMB systems.